The circular economy: quality management model in Peru - Moscoso Paucarchuco, Ketty Marilú (2019)
The circular economy is a model that seeks quality management reflected in the efficient and effective procedure of planning, organization, direction and control of an economic entity, with social and environmental responsibility, this strategy of great value reformulates the traditional linear model, With an approach oriented to modify consumption habits, to value resources and increase the useful life of products, it is an alternative solution for the care of the environment, obtaining as a result of its application a sustainable company over time.